The dollar decade : mammon and the machine in 1920s America - Best, Gary Dean (Praeger, 2003)
Examines the underlying causes of the tumult of the 1920s, including the impact of World War I, the popularization of Freud and Darwin, and in particular the cataclysmic effects of the machine age.